Особливості проростання спор мохів залежно від водного стресу, рН і температури - Хоркавців, Я.Д.; Кіт, Н.А. (Український ботанічний журнал, 2014)
Экспериментально in vitro изучали жизнеспособность одноклеточных спор мхов Funaria hygrometrica, Pohlia nutans, Ceratodon purpureus, Tortula modica. В качестве критерия способности переносить экстремальные условия среды обитания использовали прорастание спор мхов в зависи мости от влажности, кислотности субстрата и температуры воздуха. Установлено, что на низком водном потенциале Ψв = –2,5, –2,0 споры Funaria hygrometrica погибали, а жизнеспособность спор остальных видов снижалась до 5—20 %. В зависимости от влажности и рН субстрата споры Ceratodon purpureus и Tortula тodica прорастали на очень кислом рН 3,4 и высокой влажности –0,5 МПа. По мере снижения водного потенциала и повышения кислотности субстрата чувствительнее к изменению условий были споры Tortula тodica, чем Ceratodon purpureus. В условиях высокой влажности и температуры +39º С жизнеспособность спор снижалась значительно больше, чем при температуре –2º С. При повышении температуры и водном дефиците прорастание спор подавлялось, причем слабее на более низком водном потенциале. Итак, решающее значение при размножении мхов спорами имеет взаимодействие экологических факторов, широкая амплитуада влажности и рН субстрата, теплоустойчивость спор. В экстремальных условиях влажности субстрата мхи более устойчивы к высоким температурам в сухих местообитаниях. Funaria hygrometrica преобладает на влажных субстратах, на кислых почвах чаще встречается Ceratodon purpureus, чем Tortula тodica, и оба вида устойчивы к высушиванию и высоким температурам. Viability of unicellular moss spores of Funaria hygrometrica, Pohlia nutans, Ceratodon purpureus, Tortula modica has been experimentally investigated in vitro. Germination of the moss spores depending on humidity, substrate acidity and air temperature has been used as the ability criterion to bear extreme conditions of the external environment. It has been established that on low water potential –2,5, –2,0 the spores of Funaria hygrometrica have died, but spores viability of the remaining species has been lowered to 5—20%. Depending on humidity and pH of the substrate, the spores of Ceratodon purpureus and Tortula modica germinated at very acidic pH 3,4 and high humidity –0,5 MPa. The spores of T. modica have been more perceptible to the conditions variability than those of Ceratodon purpureus in the process of water potential lowering and increase of the substrate acidity. Under the conditions of high humidity and temperature +39º C, spores viability has decreased much greater than at the temperature –2º C. Under the rising temperature and water deficit, the spores germination was suppressed, being weaker at the lower water potential. Thus, the interaction of ecological factors, the wide amplitude of humidity and substrate pH, and the spores heat resistivity are of decisive significance in the process of moss reproduction. Under the extreme conditions of substrate humidity, mosses are more resistant to high temperatures in dry localities than in the humid ones. Funaria hygrometrica prevail on humid substrates, while Ceratodon purpureus occurs on acidic soils more often than Tortula modica, and both species are resistant to drying and high temperatures.